The once and future Great Lakes country : an ecological history - Riley, J. L. (John L.) (McGill-Queen's rural, wildland, and resource studies series, 2013)
"North America's Great Lakes country has experienced centuries of upheaval. Its landscapes are utterly changed from what they were five hundred years ago. The region's superabundant fish and wildlife and its magnificent forests and prairies astonished European newcomers who called it an earthly paradise but then ushered in an era of disease, warfare, resource depletion, and land development that transformed it forever. The Once and Future Great Lakes Country is a history of environmental change in the Great Lakes region, looking as far back as the last ice age, and also reflecting on modern trajectories of change, many of them positive. John Riley chronicles how the region serves as a continental crossroads, one that experienced massive declines in its wildlife and native plants in the centuries after European contact, and has begun to see increased nature protection and re-wilding in recent decades. Yet climate change, globalization, invasive species, and urban sprawl are today exerting new pressures on the region's ecology. Covering a vast geography encompassing two Canadian provinces and nine American states, The Once and Future Great Lakes Country provides both a detailed ecological history and a broad panorama of this vast region. It blends the voices of early visitors with the hopes of citizens now"--Publisher's description